Efficient and secure chaotic S‐Box for wireless sensor network. Issue 2 (28th February 2013) - Zaibi, Ghada; Peyrard, Fabrice; Kachouri, Abdennaceur; Fournier‐Prunaret, Danièle; Samet, Mounir
ABSTRACT Information security using chaotic dynamics is a novel topic in the wireless sensor network (WSN) research field. After surveying analog and digital chaotic security systems, we give a state of the art of chaotic S‐Box design. The substitution tables are nonlinear maps that strengthen and enhance block crypto‐systems. This paper deals with the design of new dynamic chaotic S‐Boxes suitable for implementation on wireless sensor nodes. Our proposed schemes are classified into two categories: S‐Box based on discrete chaotic map with floating point arithmetic (cascading piecewise linear chaotic map and a three‐dimensional map) and S‐Box based on discrete chaotic map with fixed‐point arithmetic (using discretized Lorenz map and logistic–tent map). The security analysis and implementation process on WSN are discussed. The proposed methods satisfy Good S‐Box design criteria and exceed the performance of Advanced Encryption Standard static S‐Box in some cases. The energy consumption of different proposals and existing chaotic S‐Box designs are investigated via a platform simulator and a real WSN testbed equipped with TI MSP430f1611 micro‐controller. The simulations and the experimental results show that our proposed S‐Box design with fixed‐point arithmetic Lorenz map has the lowest energy‐consuming profile compared with the other studied and proposed S‐Box design. Copyright © 2013 John Wiley & Sons, Ltd.